Proses Penyelesaian Sengketa Pembagian Harta Warisan(Studi Kasus di Pengadilan Negeri Surakarta) - Santoso, Tri Prastyo Wahyu; , Nuswardhani, S.H, S.U (2016)
There was a division of the inheritance was one in which the plaintiff to assert their rights as heirs but the defendant refused to divide the inheritance to the heirs of the other. This study aims to determine the inheritance according to Islamic law and customs of the Civil Code, to find evidence of the judge in determining the distribution of the estate, to find out the considerations judges in decisions on the distribution of the estate. The research method using descriptive approach. Using the data type of the primary and secondary data. Data collection techniques used by library research, documentation, questionnaires and interviews. Using qualitative data analysis. The results showed that the plaintiff and the defendant was the rightful heir, the division of the estate is done by the plaintiff and the defendant, judgment judge looks at the evidence in the trial, during the trial the plaintiff can prove the argument of the lawsuit, the plaintiff's claim is granted in part, the defendant declared committed acts against the law, was sentenced to divide the estate in accordance with the contents of the will.